Catalytic hydrogenation of carbon monoxide - Wayland, B.B. (Pennsylvania Univ., Philadelphia, PA (United States). Dept. of Chemistry, 1992)
This project is focused on developing strategies to accomplish the reduction and hydrogenation of carbon monoxide to produce organic oxygenates at mild conditions. Our approaches to this issue are based on the recognition that rhodium macrocycles have unusually favorable thermodynamic values for producing a series of intermediate implicated in the catalytic hydrogenation of CO. Observations of metalloformyl complexes produced by reactions of Hsub 2 and CO, and reductive coupling of CO to form metallo {alpha}-diketone species have suggested a multiplicity of routes to organic oxygenates that utilize these species as intermediates. Thermodynamic and kinetic-mechanistic studies are used in constructing energy profiles for a variety of potential pathways, and these schemes are used in guiding the design of new metallospecies to improve the thermodynamic and kinetic factors for individual steps in the overall process. Variation of the electronic and steric effects associated with the ligand arrays along with the influences of the reaction medium provide the chemical tools for tuning these factors. Emerging knowledge of the factors that contribute to M-H, M-C and M-O bond enthalpies is directing the search for ligand arrays that will expand the range of metal species that have favorable thermodynamic parameters to produce the primary intermediates for CO hydrogenation. Studies of rhodium complexes are being extended to non-macrocyclic ligand complexes that emulate the favorable thermodynamic features associated with rhodium macrocycles, but that also manifest improved reaction kinetics. Multifunctional catalyst systems designed to couple the ability of rhodium complexes to produce formyl and diketone intermediates with a second catalyst that hydrogenates these imtermediates are promising approaches to accomplish CO hydrogenation at mild conditions.